(untitled) - Subramaniam, Senthamarai Kannan; Negi, Aisha (Comptes Rendus. Mathématique, 2025)
Let $G$ be a simple algebraic group of adjoint type over the field of complex numbers, different from $\operatorname{PSL}(2,\mathbb{C})$. Let $\bar{G}$ be the wonderful compactification of $G$ constructed by C. De Concini and C. Procesi. Let $\bar{B}$ be the scheme theoretic closure of a Borel subgroup $B$ of $G$ in $\bar{G}$. Then we prove that the connected component, containing the identity automorphism of the group of all algebraic automorphisms of $\bar{B}$ is $B× B$.